Understanding the 3D Hydrodynamics of Lake Tanganyika: Insights From Modeling Circulation Patterns Using a 3D ROMS Model - Tumaini Kamulali; Paul Goodman; Joellen Russell; Andrew Cohen (Geophysical Research Letters)
Abstract This study simulates circulation patterns in Lake Tanganyika, an economically vital lake in East and Central Africa that has experienced significant warming, and reduced fishery yields in recent decades. We use Regional Ocean Modeling System to analyze thermal stratification, wind‐driven processes, and circulation dynamics within the lake. Our findings show surface temperatures ranging from ∼25.8°C to ∼27.8°C seasonally, with a notable increase of up to 0.4°C below 150 m depth between 2001 and 2020. Primary upwelling occurs in the southern region from May to August, while secondary upwelling is observed in the north from November to February. Bathymetric variations influence upwelling and downwelling processes. Our results emphasize that the interaction between atmospheric and hydrodynamic factors regulates the nutrient distribution, which is crucial for fisheries and biodiversity. We also highlight the importance of modeling in understanding the warming trends and ecological responses of Lake Tanganyika to climate change.